Investigating Students’ Motivation in Doing English Excercise Practice - Irmayanti; Zulfah Fakhruddin; Abdul Haris Sunubi; Mujahidah; Maghdahalena Tjalla (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research aims to describe the level of motivation and the type of motivation wether instrumental or integrative motivation. This research took place one of vocational high school of Polewali Mandar. The research applied descriptive quantitative design. Population of this research was 210 of students SMKS Suparman Wonomulyo. The sample of this research 40 students representtative each grade. In collecting the data qusionnaire was used as instrument. The data was calculated by using SPSS to find out percentage and frequency. The result showed that in motivation level, most students had low level. In Instrumental motivation the students had average level motivation.While, integrative motivation the students had high level motivation, and questionnaire section attitude towards English excercise practice the students generally had negative attitude.